A REVIEW ON SQL INJECTION, DETECTION AND PREVENTIONS TECHNIQUES (Journal of Pharmaceutical Negative Results, 2023)
There is several web servers in the world, and numerous website use these web servers to access the World Wide Web. These websites are open to attacks, typically of the input validation variety. These assaults make it simple to breach websites and allow anonymous user to release sensitive information. The open market is in a very risky condition right now. The analysis done as stated and on top that computerized environment leads us do research work on SQLIAs, and top of that this being more oppressed and dangerous invasion techniques, that uses runtime validation for detection of such attacks and track their event. At the same time as we shall also focus on the type of evaluation method which will be generalized and at the same time can be adapted in any existing system.